Preferensi Konsumen Terhadap Kue Wingko Babat Produksi UMKM di Lamongan - Khoiriah, Umi; Fauziyah, Elys (LP3M Universitas Putra Bangsa, 2024)
Wingko Babat MSME is one of the MSMEs that produces traditional food, which is mostly produced by home industries in the Babat District area, specifically in Lamongan Regency. One effort that can be made to develop Wingko Babat MSMEs is to pay attention to consumer preferences. This research aims to analyze consumer preferences for wingko products made by MSMEs in Lamongan and analyze the attributes that are considered important in purchasing wingko products. The sample in this study was 96 people, taken using the accidental sampling method. The analytical tool used in this research is conjoint which is used to assess consumer preferences. The results of the research show that when purchasing wingko tripe, the preferred attributes are wingko products with a price of Rp. 2000, original/coconut taste, large size (400g), aluminum foil packaging, soft texture, wet wingko differentiation, flat round shape and sales service delivery order.